(untitled) (Ibrahim Medical College Journal, 2014)
Pancreatolithiasis is a risk factor for developing pancreatic cancer. We report here a rare case of sarcomatoid carcinoma of the pancreas in a 55-year old diabetic male associated with pancreatolithiasis. CT scan of abdomen revealed a large operable mass occupying the distal body and tail of the pancreas. Per-operative survey revealed a small metastatic nodule in the surface of hepatic segment IVa. Histopathology of the distal pancreatic lesion revealed sarcomatoid carcinoma. Hepatic nodule was a metastatic adenocarcinoma. Distal pancreatectomy and splenectomy was done en-mass, along with non-anatomical resection of the hepatic metastatic nodule. Combined with six cycles of chemotherapy, the patient survived a total of another fourteen months. DOI: http://dx.doi.org/10.3329/imcj.v7i1.17742 Ibrahim Med. Coll. J. 2013; 7(1): 12-15